Genomic characterization of viruses associated with the parasitoid Anagyrus vladimiri (Hymenoptera: Encyrtidae). (6th December 2022) - Izraeli, Yehuda; Lepetit, David; Atias, Shir; Mozes-Daube, Netta; Wodowski, Gal; Lachman, Oded; Luria, Neta; Steinberg, Shimon; Varaldi, Julien; Zchori-Fein, Einat; Chiel, Elad
Abstract : Knowledge on symbiotic microorganisms of insects has increased dramatically in recent years, yet relatively little data are available regarding non-pathogenic viruses. Here we studied the virome of the parasitoid wasp Anagyrus vladimiri Triapitsyn (Hymenoptera: Encyrtidae), a biocontrol agent of mealybugs. By high-throughput sequencing of viral nucleic acids, we revealed three novel viruses, belonging to the families Reoviridae [provisionally termed AnvRV (Anagyrus vladimiri reovirus)], Iflaviridae (AnvIFV) and Dicistroviridae (AnvDV). Phylogenetic analysis further classified AnvRV in the genus Idnoreovirus, and AnvDV in the genus Triatovirus . The genome of AnvRV comprises 10 distinct genomic segments ranging in length from 1.5 to 4.2 kb, but only two out of the 10 ORFs have a known function. AnvIFV and AnvDV each have one polypeptide ORF, which is typical of iflaviruses but very un-common among dicistroviruses. Five conserved domains were found along both the ORFs of those two viruses. AnvRV was found to be fixed in an A. vladimiri population that was obtained from a mass rearing facility, whereas its prevalence in field-collected A. vladimiri was 15 %. Similarly, the prevalence of AnvIFV and AnvDV was much higher in the mass rearing population than in the field population. The presence of AnvDV was positively correlated with the presence of Wolbachia in the same individuals. Transmission electron micrographs of females' ovaries revealed clusters and viroplasms of reovirus-like particles in follicle cells, suggesting that AnvRV is vertically transmitted from mother to offspring. AnvRV was not detected in the mealybugs, supporting the assumption that this virus is truly associated with the wasps. The possible effects of these viruses on A. vladimiri 's biology, and on biocontrol agents in general, are discussed. Our findings identify RNA viruses as potentially involved in the multitrophic system of mealybugs, their parasitoids and other members of the holobiont.